2019
DOI: 10.1292/jvms.18-0621
|View full text |Cite
|
Sign up to set email alerts
|

Genetic differences between C57BL/6 substrains affect the process of testis differentiation in Y<sup>POS</sup> mice

Abstract: C57BL/6J-XY POS (B6J-XY POS ) mice, which have the Y chromosome derived from Mus musculus poschiavinus on a B6J genetic background, form ovotestes or ovaries. Previously, we replaced the genetic background of B6J-XY POS mice with B6N and found that individuals with testes also appeared in addition to those with ovaries or ovotestes. To investigate the effect of the B6J genetic sequence on the testis differentiation, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…For example, different gonadal phenotypes have appeared from the same genetic background when Mus. musculus Domesticus -type Sry, which has low stability, was replaced, such as B6-XY POS and B6-XY TIR [ 2 , 3 , 8 , 24 , 41 , 47 ]. In contrast, other strains, such as DBA/2J (D2) and 129S1/SvJ (129S), are resistant to the disturbance of sexual differentiation by M. m. Domesticus -type Sry [ 12 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, different gonadal phenotypes have appeared from the same genetic background when Mus. musculus Domesticus -type Sry, which has low stability, was replaced, such as B6-XY POS and B6-XY TIR [ 2 , 3 , 8 , 24 , 41 , 47 ]. In contrast, other strains, such as DBA/2J (D2) and 129S1/SvJ (129S), are resistant to the disturbance of sexual differentiation by M. m. Domesticus -type Sry [ 12 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, it has been reported that the timing of Sry expression and the gonadal phenotype are different in B6-XY POS mice, a model of disorders of sex development (DSD) with a B6 strain background, due to the different genetic background among B6 substrain [ 10 , 11 , 42 , 47 ]. XY POS mice with the background of the Jackson Lab strain, which is the B6J substrain, have been reported to form ovaries or ovotestes [ 10 , 11 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There are differences in the Sry sequence among mouse strains, and the capacity of testicular formation is different [1,4,30]. Sry sequences with weak activity harbored in many mouse strains with disorders of sex development may delay Sry expression and cause sex reversal, but the reason for such delayed Sry expression is unknown [2,12,36,39,40,44]. Perturbation of histone demethylase Kdm3a (lysine (K)-specific demethylase 3A; Jmjd1a) expression also causes suppression of Sry, and causes sex reversal in the male gonads [19,20,21].…”
Section: Introductionmentioning
confidence: 99%